2015
DOI: 10.1021/acs.jpcc.5b08039
|View full text |Cite
|
Sign up to set email alerts
|

Stable Pervanadyl Cation Encapsulated in Silica: Frivolous Vanadium in the H4PVMo11O40 Keggin

Abstract: Encapsulation of H 4 PVMo 11 O 40 (1-vanado-11-molybdophosphoric acid) inside silica provided a single-site long-lived pervanadyl cation (VO 2 + ) for oxidation reactions. Protective silica residues allowed vanadium to sit in the secondary Keggin structure without being reduced, contrasting the classical situation for H 4 PVMo 11 O 40 supported on silica. The vanadium of this Keggin molecule is "frivolous", tending to exit the primary structure, with one-electron reduction, even during efflorescence under ambi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Advancements in theoretical quantum chemical methods have allowed for the investigations of Wells-Dawson (and generally polyoxometalate solids) [1620], and these studies are expected to aid in the interpretation of the experimental structural and spectroscopic data. We and others have shown that 51 V solid-state NMR spectroscopy can be used as a sensitive reporter of the structural and electronic environment of vanadium sites in a wide variety of inorganic and bioinorganic solids [2139] including polyoxometalates [4042]. Specifically, in our previous MAS NMR studies on Lindqvist and Keggin polyoxotungstate solids, we have demonstrated that insights unavailable from X-ray diffraction and other structural methods could be gained, namely that counter cations and the degree of vanadium substitution modulate the electronic structure of the oxoanion as is evident in the 51 V magic angle spinning (MAS) NMR spectra [40, 41] as well as vibrational spectra [16].…”
Section: Introductionmentioning
confidence: 99%
“…Advancements in theoretical quantum chemical methods have allowed for the investigations of Wells-Dawson (and generally polyoxometalate solids) [1620], and these studies are expected to aid in the interpretation of the experimental structural and spectroscopic data. We and others have shown that 51 V solid-state NMR spectroscopy can be used as a sensitive reporter of the structural and electronic environment of vanadium sites in a wide variety of inorganic and bioinorganic solids [2139] including polyoxometalates [4042]. Specifically, in our previous MAS NMR studies on Lindqvist and Keggin polyoxotungstate solids, we have demonstrated that insights unavailable from X-ray diffraction and other structural methods could be gained, namely that counter cations and the degree of vanadium substitution modulate the electronic structure of the oxoanion as is evident in the 51 V magic angle spinning (MAS) NMR spectra [40, 41] as well as vibrational spectra [16].…”
Section: Introductionmentioning
confidence: 99%